Self-inflicted injury: An attempt of autoglossectomy !!! - S V Ravindra; G P Mamatha; B N Padmavathi; J D Sunitha; S Suresh (Wolters Kluwer Medknow Publications, 2011)
Teeth are considered as strongest, functional and unique organs of the body. In some situations, they act as injurious agents especially among the individuals with psychotic state. Oral self-mutilation is generally a diagnostic challenge for practitioners, since the incidence of oral self-mutilation in routine dental setups is uncommon. So, here we report a case of autoglossectomy in a 19-year-old male with behavioral problem.